Pengaruh Kualitas Pelayanan terhadap Loyalitas Pelanggan Jasa Transportasi Online Gojek Melalui Kepuasan Pelanggan sebagai Variabel Intervening: Studi pada Mahasiswa FISIP UPN Veteran Jawa Timur - Nibrosun Nabii; Dwiridot, Jojok (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to understand and analyze the influence of service quality on customer loyalty in Gojek's online transportation service through customer satisfaction as an intervening variable. The population in this study consists of all active students from the Faculty of Social and Political Sciences at UPN Veteran East Java, from all batches who have used Gojek's online transportation service. The sample size for this study is 100 respondents, selected using purposive sampling technique with the criteria of active students from the Faculty of Social and Political Sciences at UPN Veteran East Java, from all batches, who are customers of Gojek's online transportation service and have used it more than twice. The data analysis technique employed in this study is Structural Equation Modeling-Partial Least Square (SEM-PLS), utilizing SmartPLS 4.0 software. The results indicate that service quality significantly influences customer satisfaction, service quality does not significantly affect customer loyalty, customer satisfaction significantly influences customer loyalty, and service quality significantly influences customer loyalty through customer satisfaction in Gojek's online transportation service.